If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(a+4)-8(7-4a)=-29
We simplify the equation to the form, which is simple to understand
-(a+4)-8(7-4a)=-29
Remove unnecessary parentheses
-1a-4-8*(7-4a)=-29
Reorder the terms in parentheses
-1a-4+(-56+32a)=-29
Remove unnecessary parentheses
-1a-4-56+32a=-29
We move all terms containing a to the left and all other terms to the right.
-1a+32a=-29+4+56
We simplify left and right side of the equation.
+31a=+31
We divide both sides of the equation by 31 to get a.
a=1
| 4+14x-13x= | | 7+m/8+1=-2 | | X-8X^4=0 | | -3x-4=53 | | -3(x+6)=3-(-4) | | 15(x+27)=5x+17 | | 3(b-8)=4+7(b) | | 16w+15=7 | | 18-2k=24 | | 2.3n-11=4+n | | -2(10-9x)-6x+17= | | -5(-7x+2)=165 | | 6.1c+8=7.1c-3 | | 8(r+3)-3(3r-3)=30 | | 2x+5=75 | | 2x-18+18=84+18 | | 3(4x+3)=9x | | 2=3(4n-6)+8(5n-4) | | 4t-7=10t+5 | | 4x+3-5=29 | | x^2-x+6= | | 6x+7=42-x | | -9=-(1+8x)-2(4-4x) | | 7+x=.5(4*-2) | | 12x-4=5x-32 | | 3x+5+2x=54 | | 7x+20= | | 2x^2-17x+15=0 | | 5y+3=9y-1 | | 7+x=.5(4*2) | | 5x-1=3x+13 | | 5-4k=-(4k+1) |